Ulcerative colitis with chronic liver disease, eosinophilia and auto-immune thyroid disease. Issue 616 (February 1977) - Kane, S. P.
Abstract : A patient with chronic mild ulcerative colitis is described. Her illness was characterized by fluctuating blood eosinophilia, chronic persistent hepatitis and hypersensitivity to sulphasalazine. She subsequently developed auto-immune thyroid disease. The inter-relationships of these various disorders are discussed.